RTS des Îles - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS des Îles - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Demographic Profiles of Québec's English-speaking Communities Region of Gaspésie-Îles-de-la-Madeleine and les Îles-de-la-Madeleine - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS des Îles - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Council for Magdalen Islanders (CAMI), 2022)
In recent years, the English-speaking community of the Magdalen Islands has been engaged in a structured approach to community development. This has been guided by knowledge development and mobilization, strategic planning, and partnerships with local stakeholders to develop and implement relevant projects that meet the needs of the community.
Keywords: Official Language Minority Community (OLMC)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 11

RTS des Îles - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

CAMI Newsletter - Council for Anglophone Magdalen Islanders (CAMI) (2020)
issued: March, 2020/September, 2020 Number of pages: 12

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (Southside Navigator, 2020)
Number of pages: 6

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (Southside Navigator, 2020)
Number of pages: 6

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (Southside Navigator, 2020)
Number of pages: 6

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (Southside Navigator, 2020)
Number of pages: 6

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (2020)
Number of pages: 6

La communauté anglophone des Îles prend des mesures afin de mitiger les effets de la pandémie du COVID-19 - Council for Anglophone Magdalen Islanders (CAMI) (2020)

The English-speaking Community of the Magdalen Islands Takes Action to Mitigate the Effects of the COVID-19 Pandemic - Council for Anglophone Magdalen Islanders (CAMI) (2020)

CAMI’s Annual General Meeting : 2019-2020 - Council for Anglophone Magdalen Islanders (CAMI) (2020)

A New Organization Comes to Life on Grosse-Île : The Entreprise Sociale les îles and Its Visual Identity, Southside Experiences - Council for Anglophone Magdalen Islanders (CAMI) (2019)

Une nouvelle organisation voit le jour à Grosse-Île - Council for Anglophone Magdalen Islanders (CAMI) (2019)
Parallel title: L'entreprise sociale les îles et sond identité visuelle expériences Côte Sud

Évaluation des services communautaires pour les ainées et aînés d'expression anglaise de Gaspésie-Îles-de-la-Madeleine - Richardson, Mary; Brown, Cathy; Burke, Helena; Synnott, Jessica (Community Health and Social Services Network (CHSSN), 2019)
La présente évaluation a été entreprise à la demande des trois organismes. Elle fait suite à une évaluation antérieure réalisée en 2013 par la même auteure et couvrant un nombre moins élevé d’activités. L’évaluation a été conçue pour prendre en compte : a) l’information sur les séances de bien-être (contenu, assiduité, fréquence, etc.); b) le point de vue des personnes âgées; et c) le point de vue des animatrices (travailleuses). Les sources d’information suivantes ont été utilisées : a) relevés de présence; b) un sondage en ligne rempli en janviermars 2019 par 141 aînés; et c) des entrevues menées virtuellement par l’auteure en février 2019 avec sept animatrices et travailleuses de proximité.
Keywords: Official Language Minority Community (OLMC)

Evaluation of Community Services for English-speaking Seniors in Gaspé-Magdalen Islands - Richardson, Mary; Brown, Cathy; Burke, Helena; Synnott, Jessica (Community Health and Social Services Network (CHSSN), 2019)
This evaluation was undertaken by request of all three organizations. It follows an earlier evaluation completed in 2013 covering a smaller number of activities, by the same author. The evaluation was designed to take into account a) information on the wellness sessions (content, attendance, frequency, etc.); b) the perspectives of seniors; and c) the perspectives of the facilitators (workers). The following sources of information were used: a) attendance records; b) an online survey filled out in January-March 2019 by 141 seniors; and c) interviews conducted by the author, virtually, in February 2019 with seven facilitators and outreach workers.
Keywords: Official Language Minority Community (OLMC)

CAMI Newsletter - Council for Anglophone Magdalen Islanders (CAMI) (2019)
issued: December, 2019/January, 2020 Number of pages: 4

CAMI’s Annual General Meeting : 2018-2019 - Council for Anglophone Magdalen Islanders (CAMI) (2019)

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of the Magdalen Islands - Richardson, Mary; Maynard, Hugh; Burke, Helena; Brinklow, Laurie; Mulligan, Marleen (Council for Magdalen Islanders (CAMI), 2019)
In recent years, the English-speaking community of the Magdalen Islands has been engaged in a structured approach to community development. This has been guided by knowledge development and mobilization, strategic planning, and partnerships with local stakeholders to develop and implement relevant projects that meet the needs of the community.
Keywords: Official Language Minority Community (OLMC)

Améliorer la santé et le bien-être des Madelinots anglophones : Une stratégie pour un développement sain des jeunes - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Magdalen Islanders (CAMI), 2018)
La stratégie décrite dans le présent document est conçue comme une proposition à discuter avec les membres de la collectivité et les autres intervenants, et qui peut être adaptée et précisée au besoin. Elle est fondée sur une documentation pertinente en la matière et sur une évaluation des besoins réaliseee avec la contribution des acteurs locaux. Cette stratégie fait partie d'un processus de développement communautaire en continu, lequel a permis de réaliser un portrait de la communauté, des consultations publiques et un certain nombre d'actions qui s'inscrivent dans le cadre de la vision pour "Une communauté dynamique et en santé, sans drogues, sans alcool, ni violence, assurant un environnement favorable pour tous les membres de la communauté."
Keywords: Official Language Minority Community (OLMC)

Improving the Health and Well-Being of English-Speaking Magdalen Islanders : A Strategy for the Healthy Development of Youth - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Magdalen Islanders (CAMI), 2018)
The strategy outlined in this document is meant as a draft to be discussed with community members and other stakeholders, and to be adapted and refined as seen fit. It is based on current relevant literature, and a needs assessment carried out with input from local stakeholders. This strategy is part of an on-going community development process, which has included a community profile, community consultations, and a number of actions being carried out in the pursuit of the vision for “A dynamic, healthy community, free of drugs, alcohol and violence, with a supportive environment for all community members.”
Keywords: Official Language Minority Community (OLMC)

CAMI’s Annual General Meeting : 2017-2018 - Council for Anglophone Magdalen Islanders (CAMI) (2018)

A Needs Assessment : Better Understanding the Current Situation of the Senior Population - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Magdalen Islanders (CAMI), 2017)
This needs assessment was conducted as part of a community development process in the English-speaking community of Grosse-Ile, on the Magdalen Islands, Quebec. It is part of the follow- up to a community portrait that was developed through a participatory process in early 2015. The process involved the mobilization and engagement of a number of local stakeholders as well as community residents who expressed their views on a number of different themes. One of the issues that was highlighted by community members as a concern, even a priority, was that of the aging population within the ESC, having access to few services and limited support for caregivers.
Parallel title: Improving the Health and Well-Being of English-Speaking Magdalen Islanders
Keywords: Official Language Minority Community (OLMC)

Une évaluation des besoins : mieux comprendre la situation actuelle des aînés - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Magdalen Islanders (CAMI), 2017)
Cette évaluation des besoins a été menée dans le cadre d’un processus de développement communautaire dans la communauté anglophone de Grosse-Île, aux Îles-de-la-Madeleine, Québec. Elle fait partie du suivi d’un portrait communautaire qui a été élaboré par le biais d’un processus participatif au début de 2015. Le processus a impliqué la mobilisation et l’engagement de plusieurs intervenants locaux ainsi que de résidents de la communauté qui ont exprimé leurs opinions sur un bon nombre de thèmes. L’un des enjeux qui a été souligné par les membres de la communauté comme une préoccupation, voire une priorité, était celui du vieillissement de la population au sein de la CAI, ayant peu de services et un soutien limité aux proches aidants.
Parallel title: Améliorer la santé et le bien‑être des Madelinots anglophones
Keywords: Official Language Minority Community (OLMC)

Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

Literature Review - Mulligan, Marleen (Council for Magdalen Islanders (CAMI), 2016)
Small, rural and remote regions around the world are transforming due to forces outside of their control such as globalization, neoliberalism and climate change. While often characterized as being in a state of decline due to dwindling populations and employment opportunities, this literature review reveals that numerous small communities are finding ways to capitalize on these forces of change. The review focuses on regions similar to the Magdalen Islands – situated in the western world, shaped by colonial powers, and relatively well off. The common pattern found among the successful cases is a development approach that is internally focused, builds on existing assets (human, physical and intangible) and is scale appropriate with results that are, therefore necessarily unique to each community. These cases all include senior government support, especially in the form of funding, and in some instances, capacity building, that allows community members to carry the torch and take up the work of revitalizing their community in the ways they deem appropriate.

Regional Mini Portraits - Pocock, Joanne (2016)
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS des Îles - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Îles-de-la-Madeleine : Portrait de la communauté d'expression anglaise - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
Le présent portrait a été réalisé en collaboration avec de nombreux partenaires locaux, à l’initiative du Conseil des anglophones madelinots (CAMI) et avec l’appui du Réseau communautaire de santé et de services sociaux (RCSSS). Parmi les autres groupes ayant participé au processus figurent la Municipalité de Grosse-Île, l’école de Grosse-Île, la Corporation d’employabilité et de développement économique communautaire (CEDEC), le Centre scolaire communautaire (CSC) et l’Agglomération des Îles (comité de développement social/Les Îles en Forme).

Portrait of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed in collaboration with many local partners, through the initiative of the Council for Anglophone Magdalen Islanders (CAMI), with support from the Community Health and Social Services Network (CHSSN). Other groups involved in this process include the municipality of Grosse-Ile, the Grosse-Ile school, the Community Economic Development and Employability Corporation (CEDEC), the Community Learning Centre (CLC), Agglomération des Îles (social development committee/Les Îles en Forme).

Portrait of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed in collaboration with many local partners, through the initiative of the Council for Anglophone Magdalen Islanders (CAMI), with support from the Community Health and Social Services Network (CHSSN). Other groups involved in this process include the municipality of Grosse-Ile, the Grosse-Ile school, the Community Economic Development and Employability Corporation (CEDEC), the Community Learning Centre (CLC), Agglomération des Îles (social development committee/Les Îles en Forme). The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of the Magdalen Islands in order to create a community development plan that addresses the issues it faces.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS des Iles (1104) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

A Needs Assessment : Better Understanding Substance Use Among Youth - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Magdalen Islanders (CAMI), 2014)
This needs assessment was requested by the Council for Anglophone Magdalen Islanders (CAMI) in preparation for the development of a strategy to address substance use among young people in Gross-ile, a concern identified by community members.
Parallel title: Improving the Health and Well-Being of English-Speaking Magdalen Islanders
Keywords: Official Language Minority Community (OLMC)

Une évaluation des besoins : Pour mieux comprendre la toxicomanie chez les jeunes - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Magdalen Islanders (CAMI), 2014)
Le Council for Anglophone Magdalen Islanders - CAMI (conseil des anglophones des Îles-de-la-Madeleine) a demandé que soit effectuée la présente évaluation des besoins en prévision de l'élaboration d'une stratégie visant à contrer la toxicomanie chez les jeunes, une préoccupation soulevée par des membres de la collectivité.
Parallel title: Améliorer santé et le bien-être des Madelinots anglophones
Keywords: Official Language Minority Community (OLMC)

Baseline Data Report 2009-2010 : Demographic Profiles of Quebec's English-speaking Communities by selected CSSS Territories - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2010)
This document presents selected demographic characteristics of the English-speaking population of the CSSS territories in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI) of the Community Health and Social Services Network (CHSSN). The information presented is drawn from the 2006 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec's official language minoritty community.
Keywords: Official Language Minority Community (OLMC)

Entry Island Tragedies - Feltmate, Thelma (2009)

Entry Island School Yearbook - Entry Island School (2008)
issued: 2008/2009

Historical Heritage of English Communities On the Magdalen Islands - Currie, Wynn (2006)

Patrimoine historique des communautés anglophones des Îles de la Madeleine - Currie, Wynn (2006)

Brion Islands - Council for Anglophone Magdalen Islanders (CAMI) (2005)

Brion Islands - Council for Anglophone Magdalen Islanders (CAMI) (2005)

Rapport des activités saison 2005 - Council for Anglophone Magdalen Islanders (CAMI); Québec. Ministère du Développement durable, de l'Environnement et des Parcs (Réserve Écologique de I'Ile Brion, 2005)
En 2005, CAMI et le ministère de l'Environment du Québec ont renouvelé l'entente concernant la gestion de la réserve écologique de l'Île Brion. Le but de cette entente était de définir le rôle et les responsabilités de CAMI en ce qui a trait à l'île Brion, d'assurer la mise en place des règles d'accès et de surveillance en plus de faire valoir le programme éducatif : Vigie du golfe, gardienne du temps.

Entry Island Museum Family Names and Their History - Entry Island Historical Museum (2005)

Strategic Development Plan Oriented Towards Tourism : Phase I (2006-2008) - Gagnon, Luc (2005)
Entry Island constitutes an undeniable attraction for visitors to the Magdalen Islands, as well as for Madelinots. About 9,000 people visit the island to holiday or on excursions each year. However, the lack of appropriate facilities and services makes it difficult to receive visitors properly. Failings in this area lead to degradation of the environment and reduced quality of life for residents. Recognizing the need to receive its guests in an appropriate manner and to better direct their visit - as well as recognizing the opportunity to offer them an exclusive, quality product - the Entry Island Harbour Authority hired Luc Gagnon, an anthropology student at Universite Laval to accompany the community through a process of strategic development planning oriented towards tourism. This plan concerns Entry Island exclusively, and is meant to complement the tourism development plan adopted by Tourisme lies de la Madeleine.

They Are All Our Heroes : Lest We Forget - Morrison, Edna (2005)

Entry Island School Yearbook - Entry Island School (2004)
issued: 2004/2005

The Schools of Entry Island - Entry Island Historical Museum (2003)

Transcript of Interview with Jack McLean (2003)

Historical Heritage Sites of the Magdalen Islands' Anglophone Communities / Les sites patrimoniaux historiques des communautés anglophones des Îles-de-la-Madeleine - Clarke, Norma Jean (2003)

L'Île d'Entrée : Une vie, une époque - Entry Island Historical Museum (2002)

Entry Island School Yearbook - Entry Island School (2002)
issued: 2002/2003

Favorite Recipes from Entry Island : Reprinted by the Entry Island Historical Committee - Griffiths, W.H. (Entry Island Historical Committee, 2002)

Entry Island Life & Times - Entry Island Historical Museum (2001)

Entry Island School Yearbook - Entry Island School (2001)
issued: 2001/2002

Casseroles For All Occasions - Welsh, Ada (2001)

Entry Island Transportation & Post Offices & Hydro Quebec - Entry Island Historical Museum (Entry Island, QC, 2000)

History of Island Houses - Entry Island Historical Museum (2000)

Nurses of Entry Island - Entry Island Historical Museum (2000)

Grosse-Ile High School - Grosse-Ile High School (2000)
issued: 2000/2001

Island Tragedies at Sea - McCartney, Katherine; Pealey, Rodrick; Dickson, Jennifer; Goodwin, Robina (Council for Magdalen Islanders (CAMI), 2000)